Peranan Satgas dan TPPK dalam Permendikbudristek Nomor 46 Tahun 2023 dalam Mengatasi Diskriminasi di Lingkungan Pendidikan: Studi Kasus pada SMK Negeri 2 Padang - Dimas Okta Firdaus; Wisnu Aryo Dewanto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The controversy surrounding the hijab requirement for non-Muslim female students at SMKN 2 Padang has garnered significant public attention. This undermines the values of tolerance, particularly in education, which plays a key role in character development, particularly for students. The legal framework outlined in Minister of Education, Culture, Research, and Technology Regulation No. 46 of 2023, which includes the Violence Prevention and Handling Team (TPPK) and the Task Force, plays a crucial role in preventing and addressing violence in educational settings. This represents an effort by the central government to minimize similar discrimination and protect human rights values, which must be respected and upheld amidst the diversity of society.